Interest Group Dynamics in Regulating Digital Platforms in Brazil: Efforts to Set Rules on Online News Revenues: propostas para estabelecer regras sobre as receitas das notícias online (Intercom - Brazilian Journal of Communication Sciences, 2026)
The concentration of online content distribution and advertising revenue by platforms has fundamentally changed the traditional media landscape, triggering a crisis for publishers who relied on those revenues. Your study analyzes legislative proposals in Brazil aiming to address this complex policy battleground. The conflict over online news revenue is a prime example of a regulatory struggle driven by powerful, competing interest groups. The core of this battle lies in the redistribution of economic value and the establishment of new market rules to address the unequal bargaining power between legacy media and digital giants. Based on policymaking analysis and Latin American media regulation frameworks, we examine how legislative efforts are structuring a new logic of media policy in the country.
Keywords: Digital platforms; online news; media regulation; platform regulation.